The practices and challenges of teaching English to young learners: a case of selected primary schools in Ethiopia - Taddese, Esayas Teshome; Yassin, Habtamu Adem; Dinsa, Mitiku Tasisa; Lakew, Anteneh Kebede (Frontiers in Education, 2025)
The teaching of English to young learners requires careful consideration, as early childhood is a crucial period for acquiring a second or foreign language. In Ethiopia, however, research on this topic has been limited, with most studies focusing on secondary and tertiary education. This study, therefore, sought to examine the instructional practices of EFL teachers in relation to five widely recommended principles for teaching English to young learners, namely focusing on language use, incorporating enjoyable and varied classroom activities, integrating songs, stories, rhymes, games, and drama, utilizing objects, pictures, and actions, and establishing classroom routines. A descriptive case study design was employed, involving English teachers and school principals from primary schools. Data were collected through classroom observations and interviews, followed by a four-stage qualitative data analysis method involving coding, categorization, theme development, and interpretation. The findings revealed a significant gap between teachers’ instructional practices and the principles of effective English language teaching for young learners. While teachers demonstrated some awareness of students’ needs, their methods were largely shaped by contextual challenges and a lack of specialized training in young learner pedagogies. Addressing these gaps will require a comprehensive approach, including teacher training, improved resources, and policy reforms to foster an environment conducive to effective English instruction for young learners.